1989
DOI: 10.1002/eji.1830190724
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 induces synthesis of IgE and IgG4 in human B cells

Abstract: Interleukin (IL)4 has been shown to regulate the IgG subclasses and induce IgE production in splenic mouse B cells. Here we show that IL4 and phorbol 12-myristate 13-acetate (PMA) induce, on a per cell basis, very high IgE secretion in purified human B cells by using a mouse thymoma (EL4) co-culture method. In addition, a marked increase in the number of IgG4-producing cells was also observed. Furthermore, IL2 could synergize with IL4 and PMA in the production of IgE. By using limiting dilution analysis, a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(136 citation statements)
references
References 27 publications
6
129
1
Order By: Relevance
“…In mice, Th2 immune responses are characterized by antibodies of the IgG1 subclass (12,13); accordingly, IgG1 antibodies are found after administration of insulin (6). Although distinct antibody subclass associations with Th1 or Th2 immunity are not as clear in humans as they are in mice, the Th2 cytokine interleukin (IL)-4 can induce both IgE and IgG4 antibody production, and these antibodies are characteristic of the Th2-dominated response of atopy (14). Human IgG4 antibodies, therefore, likely represent the equivalent of a mouse IgG1 response.…”
Section: Exposure To Exogenous Insulin Promotes Igg1 and The T-helpermentioning
confidence: 99%
See 2 more Smart Citations
“…In mice, Th2 immune responses are characterized by antibodies of the IgG1 subclass (12,13); accordingly, IgG1 antibodies are found after administration of insulin (6). Although distinct antibody subclass associations with Th1 or Th2 immunity are not as clear in humans as they are in mice, the Th2 cytokine interleukin (IL)-4 can induce both IgE and IgG4 antibody production, and these antibodies are characteristic of the Th2-dominated response of atopy (14). Human IgG4 antibodies, therefore, likely represent the equivalent of a mouse IgG1 response.…”
Section: Exposure To Exogenous Insulin Promotes Igg1 and The T-helpermentioning
confidence: 99%
“…We found that, regardless of whether insulin was administered before or after diabetes onset, subcutaneous insulin therapy induced a strong IgG1-IA and IgG4-IA response. Although these findings need to be correlated with insulin-stimulated cytokine secretion, human IgG4 antibodies can be stimulated by the Th2 cytokines IL-4 and IL-13 in vitro and, together with the IgE response in allergy, are usually indicative of Th2 immunity (14,26,27). The findings could, therefore, be consistent with the hypothesis that exogenous insulin also promotes Th2 immunity in humans.…”
Section: A B C D Igg Subclass Responses To Exogenous Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…As IL-4 controls production of both IgE and IgG4 [33][34][35] and IgG4 is known to block IgE in allergic responses [36][37][38] we also analysed some individual sera for malaria-specific antibodies ofthe latter isoiype. Anu-P. falciparum antibodies have previously been shown to occur in all four IgG subclasses [39] and we have confirmed this by immunoblolting in the present investigation (noi shown).…”
Section: Ige In Cerebral Malariamentioning
confidence: 99%
“…In typhoid fever, the relative number of B220 + cells increase because IL-4 can activate B cell proliferation. Furthermore, IL-4 also provides optimal support for antibody production, and class-switching, and promotes both mast cell growth and eosinophil differentiation and activation resulting in humoral or allergic responses [43][44][45].…”
Section: Discussionmentioning
confidence: 99%